Inhibitory effect of essential oils against Lactobacillus rhamnosus and starter culture in fermented milk during its shelf-life period - Moritz, Cristiane Mengue Feniman; Rall, Vera Lúcia Mores [UNESP]; Saeki, Margarida Júri [UNESP]; Fernandes Júnior, Ary [UNESP] (Sociedade Brasileira de Microbiologia, 2012)
The use of essential oils in foods has attracted great interest, due to their antagonistic action against pathogenic microorganisms. However, this action is undesirable for probiotic foods, as products containing Lactobacillus rhamnosus. The aim of the present study was to measure the sensitivity profile of L. rhamnosus and a yogurt starter culture in fermented milk, upon addition of increasing concentrations of cinnamon, clove and mint essential oils. Essential oils were prepared by steam distillation, and chemically characterised by gas chromatography-mass spectrometry (GC-MS) and determination of density. Survival curves were obtained from counts of L. rhamnosus and the starter culture (alone and in combination), upon addition of 0.04% essential oils. In parallel, titratable acidity was monitored over 28 experimental days. Minimum inhibitory concentration values, obtained using the microdilution method in Brain Heart Infusion medium, were 0.025, 0.2 and 0.4% for cinnamon, clove and mint essential oils, respectively. Cinnamon essential oil had the highest antimicrobial activity, especially against the starter culture, interfering with lactic acid production. Although viable cell counts of L. rhamnosus were lower following treatment with all 3 essential oils, relative to controls, these results were not statistically significant; in addition, cell counts remained greater than the minimum count of 10(8)CFU/mL required for a product to be considered a probiotic. Thus, although use of cinnamon essential oil in yogurt makes starter culture fermentation unfeasible, it does not prevent the application of L. rhamnosus to probiotic fermented milk. Furthermore, clove and mint essential oil caused sublethal stress to L. rhamnosus.
Keywords: Lactobacillus rhamnosus; starter culture; essential oils; fermented milk